All-air system and radiant floor for heating and cooling in residential buildings: A simulation-based analysis. (23rd July 2020) - Alessio, Giulia; Emmi, Giuseppe; de Carli, Michele; Zarrella, Angelo
Abstract : Ventilation systems are necessary to ensure a good indoor air quality, especially in buildings characterized by high energy performance. An all-air system could be more flexible than radiant systems that need to be combined with other systems to provide fresh air and control latent loads. In this work, a multi-zone all-air system has been compared with a radiant floor integrated with mechanical controlled ventilation and an isothermal dehumidifier. All the systems have been modeled in TRNSYS considering a residential building and three different locations (Helsinki, Milan and Rome). The comparison has been performed in terms of both indoor conditions and energy consumption. The results outline that the two systems are able to maintain the desired indoor conditions. For the energy consumption, an air-to-water heat pump and all the auxiliaries have been considered. Under the same indoor conditions, in heating the electrical energy consumption of the all-air system is lower than that of the radiant floor (−19% in Helsinki, −32% in Milan and −74% in Rome); also in cooling the electrical energy consumed by the all-air system is lower in Milan and Rome (−14% and −29% respectively), whereas in Helsinki the difference is less than 5%.